Postirradiation administration of adenosine monophosphate combined with dipyridamole reduces early cellular damage in mice - Bohácek, J; Hosek, B; Pospísil, M (Life sciences, 1993)
The administration of dipyridamole and adenosine 5'-monophosphate (AMP) to mice 5 to 25 min after 1 Gy of total-body gamma irradiation was found to decrease cellular damage, as indicated by the thymidine level in plasma and the amount of saline soluble polynucleotides in the thymus. The drug combination used did not influence similar cytotoxic effects of hydrocortisone. Furthermore, it was shown that the addition of dipyridamole and AMP to in vitro irradiated suspensions of thymocytes enhanced the rejoining processes of DNA strand breaks. Receptor-mediated action of extracellular adenosine may be responsible for the therapeutic effects observed.
Keywords: dipyridamol; Mice, Inbred CBA; poškození DNA; Male; DNA Damage; Adenosine Monophosphate; mužské pohlaví; hydrokortison; Thymidine; Hydrocortisone; Dipyridamole; Animals; adenosinmonofosfát; zvířata; myši inbrední C57BL; myši; thymidin; Mice, Inbred C57BL; celotělové ozáření; Mice; Radiation-Protective Agents; Whole-Body Irradiation; radioprotektivní látky; myši inbrední CBA